2015
DOI: 10.1044/2015_aja-15-0018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Performance With an Adaptive Digital Remote Microphone System and a Digital Remote Microphone Audio-Streaming Accessory System

Abstract: Each remote microphone system improved sentence recognition in noise, but greater improvement was obtained with the digital adaptive system. The Listening in Spatialized Noise–Sentence Test Prescribed Gain Amplifier may serve as a good indicator of benefit from remote microphone technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…This is unfortunate given the poor objective and subjective speech-in-noise recognition in this group and the limited capabilities of hearing aids (even with directional microphones) to improve communication in adverse listening environments. Remote microphones have been shown to be of very high benefit, improving speech recognition and reducing listening effort in noisy environments (e.g., Wolfe et al, 2015). We strongly encourage patient education in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…This is unfortunate given the poor objective and subjective speech-in-noise recognition in this group and the limited capabilities of hearing aids (even with directional microphones) to improve communication in adverse listening environments. Remote microphones have been shown to be of very high benefit, improving speech recognition and reducing listening effort in noisy environments (e.g., Wolfe et al, 2015). We strongly encourage patient education in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…(2013) found that CI users performed better with adaptive digital wireless systems compared with analogue and fixed-gain FM systems in high levels of noise. With CI users, the general benefit from digital RM was confirmed in recent studies by Wolfe et al. (2015) and De Ceulaer et al.…”
Section: Introductionmentioning
confidence: 66%
“…In most previous studies on the effect of the Roger Pen, the device was used with the CI only (De Ceulaer et al 2016;Razza et al 2017;Wolfe et al 2015a). Another wireless microphone, the Cochlear Minimic 2þ, was also tested in bimodal CI users.…”
Section: Discussionmentioning
confidence: 99%
“…By acquiring the signal at or near the source, the signal-tonoise ratio (SNR) at the listener's ear is improved and consequently the negative effects of ambient noise, as well as those of distance and reverberation, are reduced. Previous research has shown considerable improvement in unilateral CI users' speech recognition in noise (De Ceulaer et al 2016;Razza et al 2017;Schafer and Thibodeau 2004;Schafer et al 2009;Vroegop et al 2017;Wolfe et al 2015a;Wolfe, Morais, and Schafer 2015b). A directional mode of the wireless microphone would possibly improve speech recognition even more, but specific, comparative data is lacking.…”
Section: Introductionmentioning
confidence: 99%